Since this is a function we will denote it as follows

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ) y = 5 x + 1 So, we need to show that no matter what x we plug into the equation and solve for y we will only get a single value of y. Note as well that the value of y will probably be different for each value of x, although it doesn’t have to be. Let’s start this off by plugging in some values of x and see what happens. x = -4 : y = 5 ( -4 ) + 1 = -20 + 1 = -19 x = 0: y = 5 ( 0) + 1 = 0 + 1 = 1 x = 10 : y = 5 (10 ) + 1 = 50 + 1 = 51 So, for each of these value of x we got a single value of y out of the equation. Now, this isn’t sufficient to claim that this is a function. In order to officially prove that this is a function we need to show that this will work no matter which value of x we plug into the equation. Of course we can’t plug all possible value of x into the equation. That just isn’t physically possible. However, let’s go back and look at the ones that we did plug in. For each x, upon plugging in, we first multiplied the x by 5 and then added 1 onto it. Now, if we multiply a number by 5...
View Full Document

This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.

Ask a homework question - tutors are online